Impact of Training and Development on Employees’ Performance in Epenal Group Ltd - Orlu Chukwuemeka; Green-Wike, Endurance (International Journal on Integrated Education, 2022)
The study examined the impact of training and development on employees' performance in Epenal Group Ltd., Rivers State. Four (4) research questions guided the study. A descriptive design was adopted for the paper. A sample of 300 workers, consisting of 38 dredging workers, 55 security officers, 46 staff from the piling unit, 45 from civil construction, 56 from pipeline construction, 44 boat builders, and 16 equipment leases, was drawn using random quota sampling. The instrument used for the study was a self-structured questionnaire developed by the researcher. The instrument was validated by experts, and a reliability coefficient of 0.75 was obtained using Pearson’s product moment correlation. The data collected was analysed using the mean and standard deviation. The results revealed a high influence of training and development on employees’ performance. The study found that on-the-job and off-the-job training influence the productivity of employees. The study also established that training and development positively influence employees’ job knowledge and the work quality of employees. It was recommended that employers should have compulsory training programmes for all employees in order to improve their knowledge and understanding of annual business strategy and objectives. Employees should be provided with effective training (on-the-job and off-the-job training) in order to reduce the time spent by managers on supervising employees. Employees should be provided with more training programmes in order to reduce the cost of recruiting and training new staff members.